Identification of chemoautotrophic microorganisms from a diffuse flow hydrothermal vent at EPR 9 degrees North using 13C DNA Stable Isotope Probing and Catalyzed Activated Reporter Deposition-Fluorescence in situ Hybridization - Richberg, K P (Massachusetts Institute of Technology and the Woods Hole Oceanographic Institution, 2010)
At deep‐sea hydrothermal vents chemolithoautotrophic microbes mediate the transfer of geothermal chemical energy to higher trophic levels. To better understand these underlying processes and the organisms catalyzing them, this research used DNA Stable Isotope Probing (SIP) combined with Catalyzed Activated Reporter Deposition‐Fluorescence in situ Hybridization (CARD‐FISH) to identify the microorganisms chemoautotrophically supporting the food web at a diffuse flow hydrothermal vent. Both anaerobic and aerobic shipboard incubations containing various augmented electron donor and acceptor species showed that Epsilonproteobacteria were the dominant chemoautotrophs with greater than 70{%} of the cells counted within the first 24 hours. 13C DNA SIP identified unique organisms not previously characterized from low temperature diffuse flow venting: green sulfur bacteria (Chlorobi‐like organisms) possibly utilizing photoautotrophy, aerobic Lutibacter litoralis‐like organisms growing under anaerobic conditions, and Epsilonproteobacterial Thioreductor sp. at temperatures above maximum known tolerances. This research illustrates both the promise and pitfalls of the SIP technique applied to hydrothermal systems, concluding that timing of the incubation experiments is the critical step in eliminating undesired 13C labeling. These results set the stage for a more thorough future examination of diffuse flow microorganisms by presenting interesting questions that second generation experiments could be designed to answer.
Keywords: HOV Alvin (Human Occupied Vehicle)